Implementation of Sports Science and Technology Integration Infrastructure: A Case Study of Speed Skating Utilizing Web and Mobile Applications, and Information Visualization Technologies - Kim, Minkyu; Park, Soojung (Journal of Web Engineering, 2024)
In the field of sports, there is an active discussion on and an attempt to apply technologies that integrate sports with cutting-edge science and technology for the purpose of enhancing athletic performance. In line with this trend, South Korea is supporting research on the fusion of sports and science technology at an interdepartmental level. For the improvement of performance in elite sports, it is important to consider the athlete’s skills, the coach’s information analysis, the scientification of equipment, and the environmental optimization. Accordingly, this study aims to propose web and mobile app technologies to establish an integrated infrastructure of sports science and technology for the three factors of athletes, equipment, and environment to improve the performance of speed skating. Furthermore, it aims to make policy recommendations to activate this integration. The application of such technologies and policy recommendations can be transferred and organically integrated into other sports, including track and field, which are time-based competitions. Additionally, it is expected that this approach will lead to the formation of new theories that consider the emotional aspects occurring in sports situations.